A Massive Number of Extracellular Tropheryma whipplei in Infective Endocarditis: A Case Report and Literature Review - Hannachi, Nadji; Arregle, Florent; Lepidi, Hubert; Baudoin, Jean-Pierre; Gouriet, Frédérique; Martel, Hélène; Hubert, Sandrine; Desnues, Benoit; Riberi, Alberto; Casalta, Jean-Paul; Habib, Gilbert; Camoin-Jau, Laurence (Frontiers in Immunology, 2022)
Whipple’s disease (WD) is a chronic multisystemic infection caused by Tropheryma whipplei. If this bacterium presents an intracellular localization, associated with rare diseases and without pathognomonic signs, it is often subject to a misunderstanding of its physiopathology, often a misdiagnosis or simply an oversight. Here, we report the case of a patient treated for presumed rheumatoid arthritis. Recently, this patient presented to the hospital with infectious endocarditis. After surgery and histological analysis, we discovered the presence of T. whipplei. Electron microscopy allowed us to discover an atypical bacterial organization with a very large number of bacteria present in the extracellular medium in vegetation and valvular tissue. This atypical presentation we report here might be explained by the anti-inflammatory treatment administrated for our patient’s initial diagnosis of rheumatoid arthritis.